Combining phase information in reciprocal space for molecular replacement with partial models. (1st September 2015) - Millán, Claudia; Sammito, Massimo; Garcia‐Ferrer, Irene; Goulas, Theodoros; Sheldrick, George M.; Usón, Isabel
<x xml:space="preserve">Abstract</x> ARCIMBOLDO allows ab initio phasing of macromolecular structures below atomic resolution by exploiting the location of small model fragments combined with density modification in a multisolution frame. The model fragments can be either secondary‐structure elements predicted from the sequence or tertiary‐structure fragments. The latter can be derived from libraries of typical local folds or from related structures, such as a low‐homology model that is unsuccessful in molecular replacement. In all ARCIMBOLDO applications, fragments are searched for sequentially. Correct partial solutions obtained after each fragment‐search stage but lacking the necessary phasing power can, if combined, succeed. Here, an analysis is presented of the clustering of partial solutions in reciprocal space and of its application to a set of different cases. In practice, the task of combining model fragments from an ARCIMBOLDO run requires their referral to a common origin and is complicated by the presence of correct and incorrect solutions as well as by their not being independent. The F‐weighted mean phase difference has been used as a figure of merit. Clustering perfect, non‐overlapping fragments dismembered from test structures in polar and nonpolar space groups shows that density modification before determining the relative origin shift enhances its discrimination. In the case of nonpolar space groups, clustering of ARCIMBOLDO solutions from secondary‐structure models is feasible. The use of partially overlapping search fragments provides a more favourable circumstance and was assessed on a test case. Applying the devised strategy, a previously unknown structure was solved from clustered correct partial solutions.